2008
DOI: 10.1007/s11947-008-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Variables on Heat-Transfer Rates to Canned Particulate Newtonian Fluids During Free Bi-axial Rotary Processing

Abstract: Effect of process variables on overall (U) and fluid-to-particle (h fp ) heat-transfer coefficients in canned particulates suspended in Newtonian fluids (glycerin solutions at concentrations of 80-100%) undergoing free axial rotation was evaluated in a pilot-scale rotary autoclave. Six influencing factors affecting U and h fp were selected using L 16 Taguchi model for detailed evaluation. With the significant factors identified, a response surface methodology and two full-factorial experimental designs of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The geometry benefit seen at 6 RPM is negatively impacted as rotational speed is increased with a tip over point somewhere between 6 and 11 RPM. Ramaswamy and Dwivedi (2011) showed that rotation speed has a significant impact on the overall heat transfer coefficient in a retort environment, further confirming these results.…”
Section: Average Time To Lethality By Process At 6 Rpmsupporting
confidence: 73%
See 1 more Smart Citation
“…The geometry benefit seen at 6 RPM is negatively impacted as rotational speed is increased with a tip over point somewhere between 6 and 11 RPM. Ramaswamy and Dwivedi (2011) showed that rotation speed has a significant impact on the overall heat transfer coefficient in a retort environment, further confirming these results.…”
Section: Average Time To Lethality By Process At 6 Rpmsupporting
confidence: 73%
“…If a product was processed in a traditional retort process, nutrients could be degraded as microorganisms were eliminated to render the food commercially sterile. In this example, one possible alternate to maintain preserve some nutrient integrity would be to use higher temperatures at shorter processing times (Ramaswamy and Dwivedi, 2011). In an effort to further minimize quality impact on retorted foods, the thermal processing industry has continued to develop retorts and thermal processes which optimize sterilization times and retain the maximum amount of food quality (Singh et al, 2014) Another possible strategy for delivering optimized heating to a food product could be the use of packaging type and geometry.…”
Section: Introductionmentioning
confidence: 99%
“…As RSA and Taguchi analysis methods (using ANOVA with orthogonal fractional factorial designs) have different advantages and disadvantages; they can be both used to provide different information on a given system, as done for instance by Ramaswamy and Dwivedi (2009).…”
Section: Choice Of Experimental Design and Data Analysis Methodsmentioning
confidence: 99%
“…Statistically, a good model will have a large predicted R 2 and a low RMS. With the new approach developed to measure the U and h fp in free axial mode, a simple full factorial design (3×3 factorial) was used to test their response to input variables (a more detailed evaluation of factors affecting U and h fp in free axial mode is detailed in the accompanying paper, Ramaswamy and Dwivedi 2008). Statistical analyses used to obtain means, SD of means, and analysis of variance were performed through the statistical package of SAS.…”
Section: Measured Particle Center Temperature In Fixed Axial Modementioning
confidence: 99%